CRISPR/Cas9-Mediated Mutagenesis of MdCNGC2 in Apple Callus and VIGS-Mediated Silencing of MdCNGC2 in Fruits Improve Resistance to Botryosphaeria dothidea - Zhou, Huijuan; Bai, Suhua; Wang, Nan; Sun, Xiaohong; Zhang, Yugang; Zhu, Jun; Dong, Chaohua (Frontiers in Plant Science, 2020)
Cyclic nucleotide-gated ion channels (CNGCs) have been reported to be involved in multiple plant physiological processes. Their involvement in plant immunity has been studied in several herbal plant species. It remains unclear whether CNGCs in woody plants play a similar role in plant immunity. In the present study, we identified an apple CNGC (designated as MdCNGC2), which is the homologue of Arabidopsis CNGC2. Analysis of tissue distribution revealed that MdCNGC2 was expressed in all tested tissues. Abundant transcripts of MdCNGC2 were observed in leaves and shoot bark. Low expression was observed in fruits and roots. MdCNGC2 expression was induced in apple callus and shoot bark by Botryosphaeria dothidea. The induction of MdCNGC2 was significantly higher in susceptible cultivars ‘Fuji’, ‘Ralls Janet’, and ‘Gala’ compared to the resistant cultivar ‘Jiguan’, suggesting that MdCNGC2 may be a negative regulator of resistance to B. dothidea. MdCNGC2 mutagenesis mediated by gene editing based on CRISPR/Cas9 system led to constitutive accumulation of SA in apple callus. A culture filtrate of B. dothidea (BCF) induced the expression of several defense-related genes including MdPR1, MdPR2, MdPR4, MdPR5, MdPR8, and MdPR10a. Moreover, the induction of these genes was significantly higher in mdcngc2 mutant (MUT) callus than in wild type (WT) callus. Further analysis showed that the spread of B. dothidea was significantly lower on MUT callus than on WT callus. Knock-down of the MdCNGC2 gene reduced lesions caused by B. dothidea in apple fruits. These results collectively indicate that MdCNGC2 is a negative regulator of resistance to B. dothidea in apple callus.